Faktor Penyebab Ketidaksesuaian Pencatatan Sensus Harian Rawat Inap Faktor Penyebab Ketidaksesuaian Pencatatan Sensus Harian Rawat Inap - Flower Desma Sihaloho; Kajol Santa Monika Marbun (Yayasan Literasi Sains Indonesia, 2023)
The daily census of inpatients is a means of supplementing medical records in reporting. Given the importance of the inpatient census, its management should be supported by medical record officers who have good knowledge and skills. The method obtained from 3 journals was then analyzed by descriptive method. The method used is Literature Study, carried out with a data set technique to review books, literature search, notes and reports related to research. From some of the literature studied, it was found that there was a discrepancy in the implementation of the inpatient daily census, this can be seen from the indiscipline in filling out the Inpatient Daily Census due to the absence of fixed procedures and technical instructions containing all activities that must be carried out by inpatient ward officers. Other factors are: Man, Money, Methode, inadequate human resources, no socialization of inpatient daily census recording officers with ward nurses, minimal infrastructure, SOPs governing the daily census have not been implemented, and the monitoring process of evaluation of the daily inpatient census is still not regularly scheduled. This is what makes most of the process of conducting the daily census of hospitalizations has not been carried out properly in hospitals.